Beyond Digital Borders: A Comparative Analysis of Legal Frameworks for Digital Evidence in Child-Related Crime Investigations - Nurlaela, Siti Chusnul; Mandala, Subianta (Pelopor Publikasi Akademika, 2025)
Digital evidence in child-related crime investigations presents unique challenges for legal systems worldwide, particularly as such crimes increasingly transcend national borders. The intangible, volatile, and jurisdictionally complex nature of digital evidence raises fundamental questions about how different legal frameworks address collection, preservation, and admissibility in these sensitive cases. Objectives. This study aims to identify and analyze key differences in legal frameworks governing digital evidence in child-related crime investigations across the European Union, United States, and United Kingdom, with specific focus on authority requirements, procedural standards, and cross-border evidence exchange mechanisms. Methods. Through comparative legal analysis of primary legal texts, case law, and secondary literature, this research examines the procedural requirements, technical standards, and jurisdictional approaches to digital evidence across the selected jurisdictions. Research Findings. The analysis reveals distinct regulatory models: the EU employs a structured judicial oversight model through instruments like the European Investigation Order and the emerging e-evidence package; the US CLOUD Act facilitates direct public-private cooperation through streamlined court orders and bilateral agreements; and the UK relies on Criminal Procedure Rules and traditional Mutual Legal Assistance Treaty processes with emphasis on maintaining strict chain of custody. Significant variations exist in authority requirements, technical standards for evidence authentication, and mechanisms for cross-jurisdictional cooperation. These jurisdictional differences create practical challenges for cross-border investigations, particularly concerning cloud-stored data and child sexual abuse material. The study proposes a harmonized approach that balances investigative efficiency with privacy protections and addresses the unique vulnerabilities of child victims, while respecting different legal traditions.